A numerical investigation on the combined effects of mose2 interface layer and graded bandgap absorber in cigs thin film solar cells - Zaabar F.I.; Yusoff Y.; Mohamed H.; Abdullah S.F.; Mahmood Zuhdi A.W.; Amin N.; Chelvanathan P.; Bahrudin M.S.; Rahman K.S.; Samsudin N.A.; Abdullah W.S.W. (MDPI AG, 2023)
The influence of Molybdenum diselenide (MoSe2) as an interfacial layer between Cu(In,Ga)Se2 (CIGS) absorber layer and Molybdenum (Mo) back contact in a conventional CIGS thin-film solar cell was investigated numerically using SCAPS-1D (a Solar Cell Capacitance Simulator). Using graded bandgap profile of the absorber layer that consist of both back grading (BG) and front grading (FG), which is defined as double grading (DG), attribution to the variation in Ga content was studied. The key focus of this study is to explore the combinatorial effects of MoSe2 contact layer and Ga grading of the absorber to suppress carrier losses due to back contact recombination and resistance that usually occur in case of standard Mo thin films. Thickness, bandgap energy, electron affinity and carrier concentration of the MoSe2 layer were all varied to determine the best configuration for incorporating into the CIGS solar cell structure. A bandgap grading profile that offers optimum functionality in the proposed configuration with additional MoSe2 layer has also been investigated. From the overall results, CIGS solar cells with thin MoSe2 layer and high acceptor doping concentration have been found to outperform the devices without MoSe2 layer, with an increase in efficiency from 20.19% to 23.30%. The introduction of bandgap grading in the front and back interfaces of the absorber layer further improves both open-circuit voltage (VOC) and short-circuit current density (JSC), most likely due to the additional quasi-electric field beneficial for carrier collection and reduced back surface and bulk recombination. A maximum power conversion efficiency (PCE) of 28.06%, fill factor (FF) of 81.89%, JSC of 39.45 mA/cm2, and VOC of 0.868 V were achieved by optimizing the properties of MoSe2 layer and bandgap grading configuration of the absorber layer. This study provides an insight into the different possibilities for designing higher efficiency CIGS solar cell structure through the manipulation of naturally formed MoSe2 layer and absorber bandgap engineering that can be experimentally replicated. 2021 by the authors. Licensee MDPI, Basel, Switzerland.